TRIM37 interacts with PTEN to promote the growth of human T-cell acute lymphocytic leukemia cells through regulating PI3K/AKT pathway - Qu, Honglan; Gao-wa, HASEN; Hou, Yanyan; Ren, Mengwei; Li, Jun; Jing, Baoshong; Du, YanDan (Frontiers in Oncology, 2023)
Background TRIM37 has been reported to be associated with the tumorigenesis of cancers. However, the role of TRIM37 in T-cell acute lymphoblastic leukemia (T-ALL) remains unclear. This study aimed to characterize the effect of TRIM37 on T-ALL. Methods TRIM37 expression in T-ALL patients and T-ALL cell lines was determined by qRT-PCR and Western blot. Knockdown or overexpression of TRIM37 was conducted by transferring small-interfering TRIM37 or lentivirus-mediated transducing into T-ALL cells. CCK-8 assay and flow cytometry assay were conducted to analyze the proliferation and apoptosis of T-ALL cells. Co-immunoprecipitation experiments were conducted to investigate the relationship between TRIM37 and PTEN and the ubiquitination of PTEN. Results Our results suggested that TRIM37 expression was upregulated in the blood of T-ALL patients and T-ALL cell lines. Knockdown of TRIM37 noticeably inhibited the proliferation and promoted apoptosis of T-ALL cells. Ectopic expression of TRIM37 promoted the proliferation and suppressed the apoptosis rate of MOLT-4 cells and enhanced the phosphorylation of AKT. Moreover, TRIM37 interacted with PTEN and accelerated the degradation of PTEN via TRIM37-mediated ubiquitination in T-ALL cells. Moreover, TRIM37 reduced the sensitivity of T-ALL cells to bortezomib treatment. Additionally, PI3K/AKT signaling pathway was involved in the function of TRIM37 in T-ALL. TRIM37 contributed to the proliferation of T-ALL cells and reduced the susceptibility of T-ALL cells to bortezomib treatment through ubiquitination of PTEN and activating PI3K/AKT signaling pathway. Conclusions Our study suggested that TRIM37 could be considered as a therapeutic target for T-ALL.